Estrus quality, non-return rate and conception rate in the incidence of repeat breeding in dairy cow after 2%povidone iodine therapy combined with prostaglandin F2α at KUD Tani Wilis Tulungagung - Zahrorona, Amira Halimah; Sri Pantja Madyawati; Pudji Srianto; Hermin Ratnani; Sunaryo Hadi Warsito; Sri Hidanah (Ovozoa: Journal of Animal Reproduction, 2025)
Repeat breeding is a condition in which cows fail to conceive after being bred three or more times. This study aims to determine the quality of estrus, non-return rate (NRR) and conception rates obtained after cows were treated with 2% povidone iodine. The study involved 30 Holstein Friesian cows, each having calved three times and experiencing repeat breeding. Cows in estrus were treated with 10 mL of 2% povidone iodine intrauterinely, followed by an intramuscular injection of 2 mL (250 mg/head) of prostaglandin F2α (PGF2α, Luteosyl) five days later. Estrus quality was observed by examining changes in vulvar mucosa color, mucus discharge, and vulvar temperature. Pregnancy diagnosis was made at 60 days. Results showed that 43.3% of cows had estrus quality score 3 (cows showed dark red vulvar mucosa, transparent mucus, temperature 38.9 ± 0.5 ºC), 23.3% had score 2 (cows showed reddish vulvar mucosa, some cloudy mucus, temperature 38.7 ± 1.0 ºC), and 33.3% had score 1 (cows showed pink vulvar mucosa, cloudy mucus, temperature 38.6 ± 0.5 ºC). Of the 30 cows, 20 had a non-return rate (NRR) of 66.7%. Based on these results, it can be concluded that 2% povidone iodine has a positive effect on estrus quality, NRR, and conception rates in dairy cows experiencing repeat breeding.